Spatial Patterns of Market Participation and Resource Extraction: Fuelwood Collection in Northern Uganda. (15th May 2017) - Miteva, Daniela A.; Kramer, Randall A.; Brown, Zachary S.; Smith, Martin D.
Abstract: While distance to markets is a key determinant of market participation for households that are dependent on natural resources, the distance to the resource stock is also essential. Thus, a household's location with respect to markets and the resource stock determines household market participation and associated resource degradation. Applying a discrete-choice framework for fuelwood collection in a developing country, we characterize the spatial pattern of market participation regimes and forest use. All else being equal, autarkic households are closest to the forest and furthest from the market, buyer households are closest to the market and furthest from the forest, and seller households are at intermediate distances. Empirical tests based on survey data from northern Uganda support the predictions from our theoretical model. Our findings have important implications for understanding the spatial patterns of forest degradation and determining the control group when designing impact evaluations of the effectiveness of development and conservation interventions.